Material Selection for Dye Sensitized Solar Cells Using Multiple Attribute Decision Making Approach - Baghel, Sarita; Jha, Ranjana; Jindal, Nikhil (Journal of Renewable Energy, 2014)
Dye sensitized solar cells (DSCs) provide a potential alternative to conventional p-n junction photovoltaic devices. The semiconductor thin film plays a crucial role in the working of DSC. This paper aims at formulating a process for the selection of optimum semiconductor material for nanostructured thin film using multiple attribute decision making (MADM) approach. Various possible available semiconducting materials and their properties like band gap, cost, mobility, rate of electron injection, and static dielectric constant are considered and MADM technique is applied to select the best suited material. It was found that, out of all possible candidates, titanium dioxide (TiO2) is the best semiconductor material for application in DSC. It was observed that the proposed results are in good agreement with the experimental findings.